A Note on the Release of Golden Langur (Presbytis geei, Khajuria) into the Wild in Tripura, India - Gupta, A. K.; Mukherjee, S. K. (Indian Forester, 1994)
There are no records of presence of naturally occurring wild population of Golden Langurs (Presbytis geei, Khajuria) in Tripura. Therefore, their operation for release in Wildlife Sanctuaries in the State has been suggested for captivity.